2017
DOI: 10.1080/24750263.2017.1387942
|View full text |Cite
|
Sign up to set email alerts
|

Sexual size dimorphism of group-living Mongolian gerbils Meriones unguicutalus (Muridae: Gerbillinae)

Abstract: Polygynous mammals often have male-biased sexual size dimorphism due to male-male competition for mates. However, fecundity selection may enlarge female body size. The Mongolian gerbil Meriones unguiculatus (Milne-Edwards, 1867) is a social rodent of promiscuous mating. Male gerbils exhibit social dominance hierarchy, which may differentiate reproductive success among male gerbils with larger males having more reproductive opportunities. This study investigated the hypothesis that social dominance hierarchy wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Consistent with our results, Matějů & Kratochvíl (2013) tested Rensch's rule in 63 species of ground squirrels (excluding the Cape ground squirrel) and found that ground squirrels generally do not conform to Rensch's rule, nor do they feature high degrees of sexual dimorphism overall. The relatively constant degree of sexual dimorphism, in Cape ground squirrels and other species of ground squirrel, may be attributable to the need for males to be able to fit into burrows dug by females (Matějů & Kratochvíl, 2013; Martínez & Bidau, 2016; Wang, 2017), for refuge or to copulate with females. Similarly, Wang (2017) suggests that female Mongolian gerbils ( Meriones unguicutalus ) may have smaller body sizes than their male conspecifics allowing them to fit into burrows dug by males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our results, Matějů & Kratochvíl (2013) tested Rensch's rule in 63 species of ground squirrels (excluding the Cape ground squirrel) and found that ground squirrels generally do not conform to Rensch's rule, nor do they feature high degrees of sexual dimorphism overall. The relatively constant degree of sexual dimorphism, in Cape ground squirrels and other species of ground squirrel, may be attributable to the need for males to be able to fit into burrows dug by females (Matějů & Kratochvíl, 2013; Martínez & Bidau, 2016; Wang, 2017), for refuge or to copulate with females. Similarly, Wang (2017) suggests that female Mongolian gerbils ( Meriones unguicutalus ) may have smaller body sizes than their male conspecifics allowing them to fit into burrows dug by males.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively constant degree of sexual dimorphism, in Cape ground squirrels and other species of ground squirrel, may be attributable to the need for males to be able to fit into burrows dug by females (Matějů & Kratochvíl, 2013; Martínez & Bidau, 2016; Wang, 2017), for refuge or to copulate with females. Similarly, Wang (2017) suggests that female Mongolian gerbils ( Meriones unguicutalus ) may have smaller body sizes than their male conspecifics allowing them to fit into burrows dug by males. Thus, for semi‐fossorial or fossorial species, burrowing may constrain sexual size dimorphism (Martínez & Bidau, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, females are less active and are observed gathering food in holes (Parrack and Thomas, 1970). Females with small body sizes could be able to reach small burrows, especially during pregnancy (Gliwicz, 1988;Wang, 2017).…”
Section: Discussionmentioning
confidence: 99%